Improvement of Postpartum Mother Comfort with Oxytosin Massage Colcaba Comfort Teory Approach - Dwi Rahayu; Yunarsih Yunarsih (LPPM STIKES KENDAL, 2020)
Postpartum discomfort can cause significant physical distress. Discomfort factor that the mother feels often causes the mother to stop breastfeeding. By stopping breastfeeding, the baby's sucking stimulation will decrease so that the milk production will decrease. The purpose of this study is to prove the Increased Comfort of Postpartum Mothers after Oxytocin Massage. The design of this study was a quasi-experimental design with pre-post test design with control group. The sampling technique was consecutive sampling, totaling 18 primiparous Postpartum mothers, divided into 2 groups (Oxytocin Massage Group and control group). The independent variable in this study is oxytocin massage and the dependent variable: maternal postpartum comfort. Data collection using a questionnaire: GCQ (General Comfort Questionarre) for the Comfort of Postpartum Mothers. The measurement of the validity of the GCQ instrument uses the product moment correlation formula, while the instrument reliability measurement uses the Cronbach alpha coefficient formula. From the results of statistical tests with the Analysis of Variance (ANOVA) parametric statistical tests, there were differences between the oxytocin massage group and the untreated group with a p value of 0.035 (p <0.05), which means that there was a significant difference in the group undergoing oxytocin massage, where an increase in comfort in postpartum mothers who do oxytocin massage.